Analisis Kreativitas Mahasiswa PGSD dalam Merancang Model Pembelajaran Bahasa Indonesia Berbasis Kontekstual - Nurjannah, Siti; Pratama, Fendy Yogha; Ichsan, Ichsan (FONDATIA, 2025)
The limited number of studies on the creativity of Primary School Teacher Education (PGSD) students in designing contextual Indonesian language learning serves as the background for this research, given its significant implications for the quality of basic education, particularly in addressing learning loss and pedagogical gaps. The aim of this study is to examine the level of creativity among PGSD students in designing learning models that integrate digital media, socio-cultural contexts, and the needs of elementary school students. This research employs a qualitative approach with a case study design. The sample consists of eight PGSD students selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the thematic analysis model of Miles and Huberman. The findings show that 75% of the students were able to design self-directed learning modules, 62% integrated digital media such as Quizizz and Canva, and 50% combined them with conventional media such as puzzles and visual aids. These results support Johnson’s theory of contextual learning and Torrance’s theory of creativity. The main conclusion is that PGSD students’ pedagogical creativity develops through hands-on practice, flexible media selection, and an awareness of student characteristics. Theoretical implications include the proposal of a blended contextual learning model, while practical implications involve recommendations for Teacher Education Institutions (LPTKs) to strengthen digital literacy training and project-based curricula. Moreover, this study opens avenues for further research on the effectiveness of hybrid learning models in remote areas.